(untitled) (Sports Law, Policy & Diplomacy Journal, 2023)
This article analyses how EU institutions have defined the so-called specificity of sport and the extent to which its recognition might have affected the application of internal market and competition law to sport after the adoption of Article 165 TFEU. The article relies on qualitative and inductive thematic analysis of 83 sport-related documents adopted by EU institutions. Four main themes have been identified: Definition of sports specificity, categorisation of sporting exceptions, contribution of sporting exceptions to the specificity of sport, and the impact of Article 165 TFEU in the application of EU sports law. Our findings suggest that the EU has defined the specificity of sport around a set of unique characteristics that differentiates sport from other industries. While the formal recognition of the specific structures of sport in the Treaties had little effect on the application of free movement and anti-trust provisions to sport, it seems to have had some impact in the recent application of state aid provisions to sport. Our findings are of relevance for existing debates on the regulation and governance of sport in Europe and the development of the so-called European Model of Sport.